Guía metodológica para la aplicación de la investigación científica como eje transversal y transdisciplinar para los primeros y segundos ciclos de la carrera de ingeniería en informática y sistemas computacionales de la universidad técnica de Cotopaxi en el año lectivo 2012-2013. - Pallasco Venegas, Mirian Susana (2014)
The study on "The application of scientific research and transdisciplinary and cross axis through the Learning Guide for First and Second Cycles of Engineering Degree in Computer Science and Computer Systems of the Technical University of Cotopaxi in the academic year 2011 -2012 " general objective is to reflect on the need for scientific research in the development of academic activities, ie during the classroom management of different subjects that the curriculum includes study of the race , on the other hand the interdisciplinary scientific research axis can better coordinate university activities learning process . The methodology used for this study was based on quantitative and qualitative, documentary and field research as well as the types of descriptive and exploratory research. Among the results found could highlight that scientific research does not apply comprehensively the methodological processes of learning, which affects the professional education, there are two subjects in the name of research methodology with three credits, and design projects throughout the academic training and at no time of transverse and interdisciplinary curriculum axes arise. The training process requires the professional integration of crosscutting issues to improve ethics and personality of students, in terms of interdisciplinary coordination and programming of various academic, methodological and learning activities with the support of a powerful tool is important such as the Scientific Research. It is not easy to use the tool as there is no guide to guide the development of actions in all subjects , but you can adopt and adapt in order to get better results in the formation of new professional.